Investigation on effects of vibration amplitude and frequency in vibration-assisted cutting of stainless steel SUS304 - Mang Shi; Xiaoye Li; Jicheng Zhang (AIP Advances)
Vibration-assisted cutting (VAC) has been proved as an efficient process to machine difficult-to-cut materials, and vibration amplitude and vibration frequency are the main parameters that significantly affect the work of the VAC process. This paper investigated the effects of vibration amplitude and frequency in machining of SUS304 by the VAC process considering continuous cutting. With the help of the FE analysis method, the cutting force and its amplitude, as well as cutting temperature, were calculated and compared to evaluate the quality of the VAC process. Results show that the largest cutting force and the cutting temperature can be reduced with the increase in vibration amplitude and frequency, which is beneficial for the life of the tool. This is mainly induced by optimization of the chip during the VAC process. A higher feeding depth will lead this tendency to be less significant. The vibration amplitude should be 0.5–0.7 times the feeding depth due to the work of the instantaneous feeding speed. On the other hand, the cutting force amplitude will increase along with the vibration amplitude, and this will lead to reliability problems of tools and workpieces. The vibration amplitude and frequency based on their effect on cutting temperature and cutting force amplitude needs to be studied.